Efecto de la técnica de fabricación sobre la porosidad y la dureza de los dientes acrílicos - Melissa Kúrzer-G (Universidad de Antioquia, 2006)
Artificial teeth is one of the most common applications of acrylic resins in Dentistry. The technique used by the manufacturers to handle the heat curing resin affects the final product properties. Several studies about acrylic resins for denture base materials have reported that when some parameters of the manufacturing technique are changed, for example the pressure, the temperature, and the powder-liquid ratio; the porosity and hardness are affected. However, in the case of acrylic teeth the effect is unknown. In this project, two parameters of the manufacturing process of artificial teeth were modified: temperature and powder-liquid ratio, and its effect on the hardness and porosity were analyzed. For measuring hardness a Knoop indenter was used, and for analyzing the porosity the Scanning Electron Microscope (SEM) technique. It was found that temperature is the variable that affects the most superficial hardness and that none of the studied variables generated internal porosity when they were modified. All the procedures were made according to Norma Técnica Colombiana 1591: Dientes de Resinas Acrílicas.